Development and Application of a Robust N‐Glycan Profiling Method for Heightened Characterization of Monoclonal Antibodies and Related Glycoproteins. Issue 7 (19th May 2014) - Shang, Tanya Q.; Saati, Andrew; Toler, Kelly N.; Mo, Jianming; Li, Heyi; Matlosz, Tonya; Lin, Xi; Schenk, Jennifer; Ng, Chee‐Keng; Duffy, Toni; Porter, Thomas J.; Rouse, Jason C.
<x xml:space="preserve">Abstract</x> A highly robust hydrophilic interaction liquid chromatography (HILIC) method that involves both fluorescence and mass spectrometric detection was developed for profiling and characterizing enzymatically released and 2‐aminobenzamide (2‐AB)‐derivatized mAb N‐glycans. Online HILIC/mass spectrometry (MS) with a quadrupole time‐of‐flight mass spectrometer provides accurate mass identifications of the separated, 2‐AB‐labeled N‐glycans. The method features a high‐resolution, low‐shedding HILIC column with acetonitrile and water‐based mobile phases containing trifluoroacetic acid (TFA) as a modifier. This column and solvent system ensures the combination of robust chromatographic performance and full compatibility and sensitivity with online MS in addition to the baseline separation of all typical mAb N‐glycans. The use of TFA provided distinct advantages over conventional ammonium formate as a mobile phase additive, such as, optimal elution order for sialylated N‐glycans, reproducible chromatographic profiles, and matching total ion current chromatograms, as well as minimal signal splitting, analyte adduction, and fragmentation during HILIC/MS, maximizing sensitivity for trace‐level species. The robustness and selectivity of HILIC for N‐glycan analyses allowed for method qualification. The method is suitable for bioprocess development activities, heightened characterization, and clinical drug substance release. Application of this HILIC/MS method to the detailed characterization of a marketed therapeutic mAb, Rituxan®, is described. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:1967–1978, 2014